Plants, pairing and phenotypes--two's company? - Grant-Downton, RT; Dickinson, H (2004)
An RNA-based communication network appears to play a crucial role in regulating gene expression and in repressing viral and transposon sequences in plant genomes. In this article, we consider the evidence that gene expression might also be controlled epigenetically at a level other than non-coding RNA species-chromosome pairing. This epigenetic communication between sequences might be based--as it is in other organisms--on the physical pairing between homologues and the transfer of information between corresponding epigenetic landscapes. We suggest that paramutation might represent just one--albeit extreme and obvious--facet of a pairing-based gene expression regulation system in plants. Further exciting evidence for pairing occurring between homologues in plants is now mounting. An appreciation that pairing interactions might be important throughout plant development could assist in understanding phenomena such as endosperm imprinting, hybrid phenotypes and inbreeding depression.